Nanocomposites – A route to better and smaller optical elements? - Werdehausen, Daniel; Burger, Sven; Staude, Isabelle; Pertsch, Thomas; Decker, Manuel (Optical Fabrication and Testing - Proceedings Optical Design and Fabrication 2019 (Freeform, OFT), 2019)
Nanocomposites offer tunable optical properties. We discuss the regime, in which they are suitable for optical systems, show that they unlock a wide range of properties, and investigate their potential for refractive and diffractive devices.
CRIS-Team Scopus Importer:2023-04-20